A study on the financial consumer protection in Malaysia with specific reference to the financial services act 2013 - Ilias, Ibtisam @ Ilyana; Amin, Naemah (Malaysian Consumer and Family Economics Association, 2016)
In recent times many countries across the world have become increasingly concerned on the protection of financial consumers. Malaysia, in that regard has passed the Financial Services Act 2013 (FSA) to fill in the lacunae in the existing legal framework. The objective of this study is to appraise the key provisions of the FSA with reference to financial consumer protection. Adopting a doctrinal and content analysis methodology, the relevant provisions of this statute, as well as related legal articles have been carefully examined. The findings of the study revealed that some principles of financial consumer protection to a certain extent have been successfully tackled, especially those on the redress mechanism with the establishment of the Financial Ombudsman Scheme (FOS). Nevertheless, being at an infancy stage, more comprehensive provisions on the remaining fundamental principles need to be developed. Therefore, several recommendations have been proposed for further improvements. This will help in ensuring a more inclusive, standardized and effective consumer protection regime. This study hopes to significantly contribute in improving the current legislative framework governing financial consumers in Malaysia.